Precipitant in acute heart failure in a multiethnic Asian urban cohort study. Issue 1 (22nd August 2011) - Leong, Kui Toh Gerard; Yan, Cao; Goh, Ping Ping
Abstract : Objectives: To identify acute heart failure (HF) precipitants in patients with a history of chronic HF, and to analyse any relationship with early outcomes. Background: There are limited studies on acute HF precipitants and the relationship with outcomes, and determining this will help to identify the avoidable precipitants and may lead to better outcomes. Methods: Patients with a history of HF and admission to the authors' hospital in 2008, with a discharge primary diagnosis of HF, were enrolled. Diagnosis of HF was prospectively defined and reviewed by two cardiology teams. Patients' case records were reviewed, or families were interviewed for 1-month follow-up outcome information. Results: 242 admissions by 185 patients constituted our study cohort. Patients were older, and 36.8% were females. The ethnic Chinese, Malay and Indian composition of the cohort were 41.3%, 35.1% and 16.1% respectively. The mean left-ventricular ejection fraction was 34.0±17.5%. Preserved left ventricular ejection fraction (≥45%) constituted 35.1% of the cohort. Acute HF precipitants were identified in 62.8% of admissions and unidentified in 37.2% admissions. Non-compliance issues and infections constituted 27.2% and 13.6% of precipitants respectively. Cardiac precipitants accounted for 10.0% admissions. Multiple precipitants accounted for 8.3% admissions. There were no significant differences in patient profile, including ethnicity and gender, and outcomes between patients with identified precipitants and patients with unidentified precipitants. Conclusion: Non-compliance issues were a major precipitant of acute HF in patients with chronic HF. Precipitants were not determined in 37.2% of admissions. There were no significant associations between the different types of precipitants and early 30-day outcomes.